Are participants concerned about privacy and security when using short message service to report product adherence in a rectal microbicide trial?. (24th August 2017) - Giguere, Rebecca; Brown III, William; Balán, Ivan C; Dolezal, Curtis; Ho, Titcha; Sheinfil, Alan; Ibitoye, Mobolaji; Lama, Javier R; McGowan, Ian; Cranston, Ross D; Carballo-Diéguez, Alex
Abstract: Objective: During a Phase 2 rectal microbicide trial, men who have sex with men and transgender women (n = 187) in 4 countries (Peru, South Africa, Thailand, United States) reported product use daily via short message service (SMS). To prevent disclosure of study participation, the SMS system program included privacy and security features. We evaluated participants' perceptions of privacy while using the system and acceptability of privacy/security features. Materials and Methods: To protect privacy, the SMS system: (1) confirmed participant availability before sending the study questions, (2) required a password, and (3) did not reveal product name or study participation. To ensure security, the system reminded participants to lock phone/delete messages. A computer-assisted self-interview (CASI), administered at the final visit, measured burden of privacy and security features and SMS privacy concerns. A subsample of 33 participants underwent an in-depth interview (IDI). Results: Based on CASI, 85% had no privacy concerns; only 5% were very concerned. Most were not bothered by the need for a password (73%) or instructions to delete messages (82%). Based on IDI, reasons for low privacy concerns included sending SMS in private or feeling that texting would not draw attention. A few IDI participants found the password unnecessary and more than half did not delete messages. Discussion: Most participants were not concerned that the SMS system would compromise their confidentiality. SMS privacy and security features were effective and not burdensome. Conclusion: Short ID-related passwords, ambiguous language, and reminders to implement privacy and security-enhancing behaviors are recommended for SMS systems.